Antiplasmodial, Trypanocidal, and Genotoxicity In Vitro Assessment of New Hybrid α,α-Difluorophenylacetamide-statin Derivatives - Carlos Fernando Araujo-Lima; Rita de Cassia Castro Carvalho; Sandra Loureiro Rosario; Debora Inacio Leite; Anna Caroline Campos Aguiar; Lizandra Vitoria de Souza Santos; Julianna Siciliano de Araujo; Kelly Salomão; Carlos Roland Kaiser; Antoniana Ursine Krettli; Monica Macedo Bastos; Claudia Alessandra Fortes Aiub; et al. (Pharmaceuticals, 2023)
Background: Statins present a plethora of pleiotropic effects including anti-inflammatory and antimicrobial responses. A,α-difluorophenylacetamides, analogs of diclofenac, are potent pre-clinical anti-inflammatory non-steroidal drugs. Molecular hybridization based on the combination of pharmacophoric moieties has emerged as a strategy for the development of new candidates aiming to obtain multitarget ligands. Methods: Considering the anti-inflammatory activity of phenylacetamides and the potential microbicidal action of statins against obligate intracellular parasites, the objective of this work was to synthesize eight new hybrid compounds of α,α-difluorophenylacetamides with the moiety of statins and assess their phenotypic activity against in vitro models of Plasmodium falciparum and Trypanosoma cruzi infection besides exploring their genotoxicity safety profile. Results: None of the sodium salt compounds presented antiparasitic activity and two acetated compounds displayed mild anti-P. falciparum effect. Against T. cruzi, the acetate halogenated hybrids showed moderate effect against both parasite forms relevant for human infection. Despite the considerable trypanosomicidal activity, the brominated compound revealed a genotoxic profile impairing future in vivo testing. Conclusions: However, the chlorinated derivative was the most promising compound with chemical and biological profitable characteristics, without presenting genotoxicity in vitro, being eligible for further in vivo experiments.